2010
DOI: 10.1111/j.1365-2206.2010.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

Youth in foster care: developmental assets and attitudes towards adoption and mentoring

Abstract: A B S T R AC TThe present study explores the relationship between the characteristics of youth in foster care and youth attitudes about mentoring and adoption. Using a positive youth development framework, the study examines the relationship between youth risk and resilience variables (youth risk scores, youth assets and youth perception of control) and youth attitudes about mentoring and adoption. Data were collected from 54 youth, ages 10 to 17 years, through intake interviews and surveys. Participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
3
10
1
Order By: Relevance
“…There was also a contradiction between the two studies in that the sample of youth in foster care in the Diehl et al (2011) study reported a sense of control over their lives while some of the participants in this current study reported that they did not feel they had control over their lives. This trend was paired with another where the youth described future participation in the system where they would have more power or control to help others.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…There was also a contradiction between the two studies in that the sample of youth in foster care in the Diehl et al (2011) study reported a sense of control over their lives while some of the participants in this current study reported that they did not feel they had control over their lives. This trend was paired with another where the youth described future participation in the system where they would have more power or control to help others.…”
Section: Discussioncontrasting
confidence: 66%
“…Therefore, the findings that a larger percentage of these youth trust someone (87.5%) and feel loved (69%) while fewer find support within their family (31%), demonstrates resilience. Although participation in the Peace4Kids program limits the generalizability of these findings to the larger population of youth in foster care, a similar finding has been reported in another study (Diehl et al, 2011). Future research can uncover where and how these sources of support are found.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Research suggests that underlying strong mentoring bonds lay partnerships built on respect, trust, honesty, reliability, consistency, empathy, authentic engagement and mentors with the ability to form close, emotional relationships (Spencer et al 2004Rhodes et al 2009;Diehl et al 2011;Johnson et al 2011;Pryce 2012;Hiles et al 2013). But mentoring does not succeed equally well for everyone.…”
Section: Endings In Youth Mentoring Relationshipsmentioning
confidence: 99%
“…Even after many considerations have been given to involving children in research in other areas of study (e.g., medical research), foster youth are still seldom involved in child welfare research (e.g. Samuels, 2009;Pecora, et al, 2010;Diehl, Howse, & Trivette, 2011). Fenton (2002 appositely surmised the following: "though the system was created for children, it is too often only about them" (p. 59).…”
Section: The Voice Of Youth: a Missing Componentmentioning
confidence: 99%